2012
DOI: 10.5539/jms.v3n1p16
|View full text |Cite
|
Sign up to set email alerts
|

Strategic versus Ad-hoc Corporate Social Performance: An Analysis of CSP Maturity and Its Relationship to Corporate Financial Performance

Abstract: This paper extends empirical research that examines the Corporate Social Performance (CSP)-Corporate Financial Performance (CFP) relationship. Previous studies display mixed findings with no unified evidence regarding the CSP-CFP relationship's direction or impact. We introduce the concepts of strategic CSP and ad-hoc CSP, which we collectively term "CSP maturity." Using panel data on 86 large European banks and insurance companies, we investigate whether there is a relationship between a company's financial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Additionally, in European countries, many studies also found mixed results between social disclosure and firm financial performance [104,105]. Garcia-Castro et al [104] examined corporate disclosure dimensions in terms of employee relations, customer, product development, community relations and diversity issues against ROE, ROA, MVA and Tobin's Q representing firm financial performance.…”
Section: Social Disclosure and Firm Financial Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in European countries, many studies also found mixed results between social disclosure and firm financial performance [104,105]. Garcia-Castro et al [104] examined corporate disclosure dimensions in terms of employee relations, customer, product development, community relations and diversity issues against ROE, ROA, MVA and Tobin's Q representing firm financial performance.…”
Section: Social Disclosure and Firm Financial Performancementioning
confidence: 99%
“…The results show weak negative results when endogeneity is suitably taken into consideration. Similarly, Skudience et al [105], sampled 86 firms consists of 62 large banks and 28 large insurance European listed firms for four years from 2005-2008. The financial data was downloaded from the reliable database (Financial Times Top 500).…”
Section: Social Disclosure and Firm Financial Performancementioning
confidence: 99%
“…Environmental performance is a demand that a company needs to fulfil as a result of pressures from employees, people, communities who concern about the environment and government as regulators [16]. Environmental performance in Indonesia can be measured A company's social performance emerges with a concept whereby a company voluntarily integrates the social and environmental concerns into its business operations as well as its interactions with the stakeholders [36]. The company's social performance illustrates how a company's performance reflects its social responsibility and how a company can optimise every opportunity related to its business and social relationships [5].…”
Section: Independent Variablesmentioning
confidence: 99%
“…Moreover, some prior studies in North America (such as Ioannou & Serafeim, 2014) discovered a negative correlation between CSR and financial performance, while other researchers discovered a similar correlation in Africa (Chetty et al, 2015; Mansaray et al, 2017; Marfo et al, 2015). Earlier empirical studies revealed a neutral link, adding to the conflicting results about the relationship between CSR and financial performance (Iqbal et al, 2012; Skudiene et al, 2013). It should be highlighted that Ghana's inconclusive CSR‐financial performance nexus is similar to the worldwide scenario.…”
Section: Introductionmentioning
confidence: 98%